A case study on the effects of glocal second language setting on the language learning motivation of foreign learners of Turkish - Takkaç Tulgar, Ayşegül (International Journal of Multicultural Education, 2018)
This case study examines the relationship between the glocal second language setting and the motivational levels of foreign learners of Turkish. Selected by purposeful sampling, the participants were 10 foreign learners of Turkish taking a year-long preparatory class in language education at AtaTömer. The content analysis of the data collected through six open-ended questions and semi-structured interviews showed that, being aware of the importance of motivation in language learning, the participants considered taking courses from native speaker teachers and having intercultural interaction with native speakers and classmates from different countries as motivating factors, while initial concerns for preserving cultural identity in the new community and some language-related difficulties were considered as demotivating factors in the glocal second language setting.